Whose Women's Bodies Belong to: FemTech's Feminist Political Economy (FPE) and Potential Risks: FemTech's Feminist Political Economy (FPE) and Potential Risks - Farah Fajriyah; Ambar Alimatur Rosyidah; Syfa Amelia (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
Femtech opens space to fulfill women's right to information on sexual and reproductive health and raises the potential for control over women's bodies. This study aims to explore the potential risks of FemTech related to women's bodies in cyberspace and uncover the exploitation and misuse of women's data. Women as users in an organized manner are seen as commodity objects, which indirectly makes women digital laborers. This study uses analysis of the Feminist Political Economy (FPE) lens from Bezanson & Luxton in three conceptual areas, namely the expansion of production models, the sex/gender system, and the analysis of domestic labor as a contribution to labor reproduction. This article develops an FPE analytical framework for studies of technology-related reproductive health. The researcher summarizes user data collected in Indonesia's top ten FemTech applications by entering the keyword' menstrual calendar' in the iOS App Store and Android Play Store. This research finds that women as Femtech users are shackled in the reality of hegemonic masculinity and lack of reproductive freedom, are in a commodity circle, and are exposed to risks as digital workers. Keyword: FemTech, Feminist Political Economy, Digital Labor, Social Reproduction